The regulatory role of bile acid microbiota in the progression of liver cirrhosis - Zhu, Feng; Zheng, Shudan; Zhao, Mei; Shi, Fan; Zheng, Lihong; Wang, Haiqiang (Frontiers in Pharmacology, 2023)
Bile acids (BAs) are synthesized in liver tissue from cholesterol and are an important endocrine regulator and signaling molecule in the liver and intestine. It maintains BAs homeostasis, and the integrity of intestinal barrier function, and regulates enterohepatic circulation in vivo by modulating farnesoid X receptors (FXR) and membrane receptors. Cirrhosis and its associated complications can lead to changes in the composition of intestinal micro-ecosystem, resulting in dysbiosis of the intestinal microbiota. These changes may be related to the altered composition of BAs. The BAs transported to the intestinal cavity through the enterohepatic circulation are hydrolyzed and oxidized by intestinal microorganisms, resulting in changes in their physicochemical properties, which can also lead to dysbiosis of intestinal microbiota and overgrowth of pathogenic bacteria, induction of inflammation, and damage to the intestinal barrier, thus aggravating the progression of cirrhosis. In this paper, we review the discussion of BAs synthesis pathway and signal transduction, the bidirectional regulation of bile acids and intestinal microbiota, and further explore the role of reduced total bile acid concentration and dysregulated intestinal microbiota ratio in the development of cirrhosis, in order to provide a new theoretical basis for the clinical treatment of cirrhosis and its complications.